Quantização Canônica - CARVALHO, Willian Oliveira de (2024)
This work aims to study the quantization of ﬁelds governed by relativistic equations. This process is done through the study of harmonic oscillators whose role is fundamental in physics of particles and ﬁelds. The development was done through canonical quantization, that is, the wave functions are promoted to operators that satisfy non trivial commuta tion (bosonic ﬁelds) or anticommutation (fermionic ﬁelds) relations. In the context of quantum ﬁeld theory, we calculate the Feynman propagator for the Klein-Gordon, Dirac and Maxwell’s ﬁelds, essential in the study of scattering processes using Feynman rules.